2007
DOI: 10.1007/s00405-007-0277-1
|View full text |Cite
|
Sign up to set email alerts
|

Donor site morbidity of the fasciocutaneous radial forearm flap: what does the patient really bother?

Abstract: The objective of this study was the evaluation of donor site morbidity in head and neck cancer patients after reconstruction using a free vascularized radial forearm Xap with emphasis on subjective complaints. Fifty patients who underwent at least 6 months before a reconstruction using a free vascularized radial forearm Xap were asked to Wll out two questionnaires regarding cosmetics and sensibility and forearm disabilities. Furthermore, a function test including movement extensions (Xexion-extension, ulnar-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 26 publications
3
57
2
Order By: Relevance
“…[7][8][9][10] In addition, it has been shown that objective measurements do not accurately reflect the patient's experience. 4,6 This may be because the majority of RFF flaps are harvested from the non-dominant arm, and the reduction in wrist motion was not severe enough to impact significantly on daily life. The present study therefore did not analyse wrist mobility because of its limited clinical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] In addition, it has been shown that objective measurements do not accurately reflect the patient's experience. 4,6 This may be because the majority of RFF flaps are harvested from the non-dominant arm, and the reduction in wrist motion was not severe enough to impact significantly on daily life. The present study therefore did not analyse wrist mobility because of its limited clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8,9 The aim of the present prospective matched-pair study was to determine the effect of the RFF flap on upper extremity function.…”
Section: Introductionmentioning
confidence: 99%
“…1 Not only does late-stage disease portend a poorer survival compared with early-stage disease, treatment of late-stage disease entails much more extensive treatment and results in a poorer quality of life. [2][3][4][5][6] Opportunities to reduce diagnostic delays in oral cavity cancer may exist for which detecting more disease at an earlier stage could result in improved survival and reduced morbidity. Few studies have examined the diagnostic pathway of oral cavity cancer and assessed whether delays commonly occur in the US population.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques such as direct closure, prelamination or full thickness skin graft (FTSG) instead of split thickness skin graft (STSG) at RFF donor defect have been employed, but STSG is still the method of choice for many surgeons [2][3][4][5], including those at our institute, Seoul National University Dental Hospital.…”
Section: Introductionmentioning
confidence: 99%